PERSEPSI WAJIB PAJAK ORANG PRIBADI TENTANG PELAKSANAAN SELF ASSESSMENT SYSTEM TERHADAP TINDAKAN TAX EVASION DI KULON PROGO - Dini Utami; Andri Waskita Aji (Jurnal Akuntansi, 2015)
This research aimed to determine the individual tax payer perceptions about the implementation of self assessment system to measure tax evasion in Kulon Progo. Variables that are used to represent the taxpayer's perception is tax regulations, the service tax authorities, the effectiveness of the tax system. Sampling using purposive sampling and data collection using the questionnaire. The questionnaire distributed to the individual tax payer who is in Kulon Progo. Technical analysis of the data in this research is multiple linear regression analysis using SPSS 20 for windows. The results showed that the tax regulations negatively affect tax evasion acts are of significant, negative effect on the service tax authorities of tax evasion significant action, the effectiveness of the tax system significantly influence the actions of tax evasion significantly. The ability of the regression equation to explain the effect of tax laws, the service tax authorities and the effectiveness of the tax system amounted to 77.55%, while 22.5% is explained by other variables outside the research. Keywords: tax regulations, tax authorities and the effectiveness of the service system of taxation.